EFFECTIVENESS OF EXTENSION WITH DENTAL HEALTH EDUCATION VIDEO MEDIA ON ORAL HYGIENE AND SKILL CLEANING LEVELS IN DENTAL TUNAGRAHITA STUDENTS IN SLB BALI PROVINCE - I Gede Surya Kencana; I Made Budi Artawa; Ida Ayu Dewi Kumala Ratih; I G A A Raiyanti (Jurnal Kesehatan Gigi (Dental Health Journal), 2020)
Dental health is one of most important things for childrens growth, but in Indonesia there are not many parents who care about childrens dental health, especially in childrens with special needs (disabled children). Childrens with special needs have a higher risk of oral and dental health problems,because they have mental and physical shortcomings and limitations to perform optimal self-cleaning teeth. The purpose of this study was to determine the effectiveness of counseling with Dental Health Education video media on tooth brushing behavior and the level of oral and dental hygiene in middle-class mental retirement students in the province of Bali in 2019. This type of research is an experimental community trial with pretest-posttest control group design . The results of research on Tunagrahita students are in the medium category of SLB in Bali Province as many as 200 people. The education level of the respondents consisted of SDLB, SMPLB and SMALB.  Students' skills in brushing their teeth before the intervention in the treatment group 100 (100%) need guidance, after the intervention 6 (6%) categories are good, 13 students in the sufficient category and 81 (81%) need guidance. The level of dental hygiene of retarded students was in the moderate category in the treatment group before the intervention with good criteria 15 people, moderate 68 (68%) and bad criteria17 (17%), after the intervention with good criteria 36 (68%), moderate 56 (56%) and bad criteria 8 (8%). The average level of dental hygiene in the treatment group before the intervention was 2.26 and after the intervention 1.87. The Wilcoxon Signed Rank Test statistic results showed that the analysis results obtained a p value (Asymp.sig 2 tailed) of 0,000 less than 0.05. Conclusion there are significant differences in both the skills and oral and dental hygiene in the treatment group and the control group after the intervention is given.